ABCC8 Gene Factors in Maturity-Onset Diabetes of The Young (MODY): Literature Review - Setyawati, Tri; Walanda, Ryka Marina; Sulisda, Sulisda; Putrie, Intania Riska; Oktafiani, Devi (Media Publikasi Cendekia Indonesia, 2025)
Maturity-Onset Diabetes of the Young (MODY) is a monogenic form of diabetes caused by single-gene mutations affecting insulin secretion, often presenting in young individuals. Mutations in the ABCC8 gene (MODY12), encoding the SUR1 subunit of the pancreatic β-cell K-ATP channel, are a known cause, though relatively rare (1-3% prevalence). This literature review summarized cases of ABCC8-MODY, detailing genetic/clinical features, differentiating it from Type 1 (T1DM) and Type 2 (T2DM) diabetes, and outlining treatments. A Google Scholar search (2020-2024) using keywords